Measuring 'empowerment' using quantitative household survey data - Mahmud,Simeen; Tasneem, Sakiba (© 2014 Elsevier Ltd., 2016)
This article was published in Women's Studies International Forum [ © 2014 Elsevier Ltd. ] and the definite version is available at: http://doi.org/10.1016/j.wsif.2013.11.009 The Article's website is at: http://www.sciencedirect.com/science/article/pii/S0277539513002094